ANALISIS PEWARNA DAN PEMANIS BUATAN PADA SAUS CABAI BAKSO BAKAR DAN “SAUS GEJROT TAHU DANGDUT” YANG DIJAJAKAN DI KAWASAN USU TAHUN 2015 - Febri Hakiki; Evawany Y Aritonang; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Chili sauce and “saus gejrot” (spattered sauce) is a food processing product which popular among the students of USU (University of Sumatera Utara) because it is used in the students’ favorite snacks, grilled bakso (meat ball) and “tahu dangdut” (the name of a kind of tofu). Generally, the process of making the sauce added dyes and artificial sweeteners to get the maximum results with low production costs .          The research was a descriptive survey in order to find out whether or not there was coloring matter in chili sauce of grilled bakso and artificial sweetener in “saus gejrot” of “tahu dangdut” sold at USU in 2015 by conducting laboratory test qualitatively and quantitatively. The unit of analysis in this study are some of the chili sauce from 5 chili sauce used on grilled meatballs and some " saus gejrot " from 7 " saus gejrot " used to " tahu dangdut " in the USU 2015 . The result of the research showed that all samples got their license from the Department of Health through the PERMENKES RI No. 033/2012 on Food Additives. There are 4 of 5 portions the chili sauce were used artificial dyes with level that exceed the maximum limit used is 200 mg/kg. That is Tradisional chili sauce, Captain, Selera Kita and Sasa. The results of the examination 7 portions of “saus gejrot”, all of them used artificial sweetener, cyclamate with levels still below the maximum limit of use is 3 g/kg. Cyclamate levels are lowest for the “saus gejrot” sold at Pajus is 0,1328 g/kg and the highest levels of cyclamate sold at Pintu 1 is 0,2960 g/kg. It is recommended that the management of BPOM (Food and Drug Monitoring Agency), Medan, increase monitoring and supervision on the use of coloring matter and artificial sweetener in sauce products. The Health Service of Medan and the Health Service of North Sumatera should provide counseling for chili sauce and “saus gejrot” producers about impact the use of coloring matter and artificial sweetener as food additives. Keywords: Chili Sauce, “Saus Gejrot”, Artificial Sweetener, Cyclamate, USU